2019
DOI: 10.1007/s13595-019-0869-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate has a larger effect than stand basal area on wood density in Pinus ponderosa var. scopulorum in the southwestern USA

Abstract: & Key message Stand basal area of ponderosa pine (Pinus ponderosa var. scopulorum Engelm.) in the US Southwest has little effect on the density of the wood produced, but climatic fluctuations have a strong effect. Wood density increases during drought, particularly if the drought occurs in late winter/early spring. Future droughts, as are predicted to increase in the US Southwest, may lead to production of smaller radial increments of higher density wood in ponderosa pine. & Context Forest restoration treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…However, average CWD for the Diospyros genus is higher in humid bioclimates, where there is more precipitation, than in subhumid bioclimates. These results are in line with previous research by Vaughan et al (2019) who observed an increase in wood density during drought conditions. Similarly, Ibanez et al (2016) found that aridity conditions characterized by low precipitation and high temperatures promote the formation of highdensity wood.…”
Section: Radial Wood Density Variationsupporting
confidence: 94%
“…However, average CWD for the Diospyros genus is higher in humid bioclimates, where there is more precipitation, than in subhumid bioclimates. These results are in line with previous research by Vaughan et al (2019) who observed an increase in wood density during drought conditions. Similarly, Ibanez et al (2016) found that aridity conditions characterized by low precipitation and high temperatures promote the formation of highdensity wood.…”
Section: Radial Wood Density Variationsupporting
confidence: 94%
“…Two papers addressed this knowledge gap. Vaughan et al (2019) showed in Pinus ponderosa that it is not growth rate, per sé, which is closely tied to variation in wood properties (in their case, focussing on wood density as an indicator) but rather annual climate peculiarities which lead to variation in the timing and extent of transitions into latewood production. Erasmus et al (2020), looking at Pinus patula, found a clear effect of tree spacing.…”
mentioning
confidence: 99%